Effect of non genetic factors on productive traits of Black Bengal goats (Journal of the Bangladesh Agricultural University, 2014)
Accumulated five years data on 197 kids of 15 Black Bengal bucks in the nucleus breeding flock of Black Bengal goats were analyzed for the study of production traits. The traits considered were birth weight, weight at every 3- month interval up to 12-month, semen characteristics and milk yield. Semen parameters were evaluated from 450 ejaculates of 15 Black Bengal bucks collected twice a week by artificial vagina method and daily milk yield of Black Bengal goats were estimated from the analysis of 57 lactation records of 30 does. The significance of fixed effects sex of kid, parity, litter size, season, age, body weight and scrotal circumferance were analyzed using least-squares analyses of variance of the general linear model (GLM) procedure of the Statistical Analysis System (SAS, 1998). Least-squares means for body weights at birth, 3, 6, 9 and 12-month of age were 1.3, 4.8, 8.0, 11.1 and 14.0 kg, respectively. Body weights at 3, 6, 9 and 12-month of age except at birth were affected by the sex of kids (p